One year of SARS-CoV-2 pandemic: comparison of infection between health care workers and general population before and after vaccination - Visci, Giovanni; Zunarelli, Carlotta; Violante, Francesco; Boffetta, Paolo (La Medicina del Lavoro, 2021)
Background: The Covid-19 pandemic in Italy has been characterized by three waves of infection during 2020. Vaccination of healthcare workers started in January 2021, earlier than that of other population groups. The main aim of this study is to compare the spread of the pandemic between HCW and the general population focusing on potential effects of the vaccination. Methods:The study consisted of a retrospective analysis of results of RT-PCR tests performed between 6 March 2020 and 4 April 2021 among HCWs from Bologna, Italy, and those of the general population of Emilia Romagna region. We calculated the crude proportion of positive RT-PCR tests over total tests and the crude prevalence of positive test in population; then, we conducted joinpoint analyses using the Joinpoint Regression Program of the National Cancer Institute. Results: The results of the joinpoint analysis show that both φ and ψ ratio indicators have a similar pattern, with a sharp increase during the early phase of the pandemic, and a strong decrease at the end of the first wave around week 15. In both indicators there are no significant changes in the trend after week 25. Pandemic spread among HCWs appeared earlier than in the general population, but it otherwise appeared to have comparable features. A decline in infection was apparent among HCWs after vaccination. Conclusions: Surveillance of HCWs would inform on the epidemic in the general population. The apparent effectiveness of the anti-SarsCoV2 vaccine will likely occur in the general population.